Synthesis of silica/carbon composite from agricultural waste as heterogeneous acid catalysts to produce dioxolane moieties from a biodiesel-derived waste compound (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Silica/carbon composites from the carbonization of rice husk have been employed to act as heterogeneous Brønsted acid catalysts. These composites have been used to catalyze the acetalization of phenylacetaldehyde, vanillin, and 2 acetonaphthone with propylene glycol to produce hyacinth, vanilla, and orange blossom scent fragrances. As the carbonization temperatures affect the physicochemical properties and hence their catalytic activity, several characterization techniques and data manipulation have been performed to understand the correlations. Acid density and hydrophilicity has been proved to play a crucial part to obtain an optimized yield of desired products.